The Influence of Debtor Quality, Income Level, and Collateral on the Decision to Grant Loan Credit at BRI Kelapa Unit KC Bumi Serpong Damai - Harian Syaputra; Sugeng Susanto; Ikmalia Inayah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the influence of debtor quality, income level, and collateral on credit lending decisions at Bank Rakyat Indonesia (BRI) Unit Kelapa Dua, KC Bumi Serpong Damai. The findings indicate that debtor quality and collateral have a positive and statistically significant effect on credit approval decisions, while income level does not exhibit a significant influence. These results suggest that banks prioritize behavioral credibility and asset-based guarantees over income considerations when assessing loan applications. Collectively, the three variables significantly affect credit lending decisions, confirming the importance of comprehensive credit evaluation frameworks in mitigating credit risk and maintaining banking stability.The results of this study contribute to the literature on credit risk management by reinforcing the relevance of prudential principles, particularly the application of the 5C framework, in contemporary banking practices. The insignificance of income level highlights the need for banks to refine income assessment mechanisms, especially for borrowers with fluctuating or informal earnings. Future research is encouraged to incorporate additional variables such as business prospects, macroeconomic conditions, and digital credit scoring systems to further enhance the understanding of credit decision-making processes in the banking sector.